Developing a Generation Z-Friendly Da’wah Concept Based on Buya Hamka’s Perspective in Tafsir Al-Azhar - Yuliantika, Anindhita Arina; Ridho, Muhammad Mukharom; Parwanto, Parwanto; Masuwd, Mowafg Abrahem (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan Jawa Timur, 2025)
The concept of da’wah is very important in the spread of Islamic knowledge. The occurrence of several mistakes by preachers, especially when they preach to generation z, makes this research important to discuss. Generation z has its own characteristics that result in methods to preach to them must use different methods. Thus, this study aims to examine the concept of gen z friendly da’wah based on Buya Hamka’s perspective in Tafsir Al-Azhar. This research uses a literature study method with an analytical-descriptive approach to explore Buya Hamka’s thoughts, especially related to gen z friendly da’wah methods with the social context of Indonesian society. Tafsir Al-Azhar was chosen as the main reference because of its adab ijtima’i approach that focuses on social issues. The results showed that Buya Hamka offered three main concepts in da’wah, namely first da’wah with wisdom, which prioritizes wisdom, common sense, and a clean heart. Second, da’wah with mau’izhah hasanah, which is giving advice and teaching in a good and polite way. And third, da’wah with mujadalah billati hiya ahsan, namely preaching by discussing or arguing in the best way, full of patience, and respect. These three concepts are considered by Buya Hamka to be relevant for all generations, so this research has important contributions and contributions in the concept of da’wah for generation Z.